2015
DOI: 10.1155/2015/904273
|View full text |Cite
|
Sign up to set email alerts
|

Yiqihuoxuejiedu Formula Restrains Vascular Remodeling by Reducing the Inflammation Reaction and Cx43 Expression in the Adventitia after Balloon Injury

Abstract: Vascular remodeling is closely related to hypertension, atherosclerosis, and restenosis after PCI. Considerable evidence indicates that the activation and proliferation of adventitial fibroblasts play key roles in vessel injury. The inflammatory response and high expression of connexins contribute to adventitial remodeling. Therefore, reducing inflammation reaction and connexins expression in adventitia may become a new target to prevent vascular remodeling. Yiqihuoxuejiedu formula, composed of TCM therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Routine HE staining was performed as previously reported (Chang et al, ). Immunohistochemical Staining was used to detect the expression of α‐smooth muscle‐actin (α‐SMA) in the vascular wall.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine HE staining was performed as previously reported (Chang et al, ). Immunohistochemical Staining was used to detect the expression of α‐smooth muscle‐actin (α‐SMA) in the vascular wall.…”
Section: Methodsmentioning
confidence: 99%
“…It used to be though that medial smooth muscle cells (SMC) were the main cells involved in formation of neointima. However, recent studies have found the adventitia cells play an important role in vascular remodeling (Coen et al, ; Wang et al, ; Zhao et al, ; Chang et al, ). Researches show that adventitial fibroblast (AF) is a sentinel cell and it immediately activates into myofibroblasts and may migrate in response to various stimuli.…”
mentioning
confidence: 99%
“…Numerous investigations describe the role of the adventitia in the development of restenosis after a balloon angioplasty (Shi et al 1996;Fleenor and Bowles 2009;Chang et al 2015); however, few studies have evaluated this vascular layer after a stent implantation (Hofma et al 1998;Nishimiya et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information about the media and (neo)intimal response to coronary stent implantation can be found elsewhere (Estevez-Loureiro et al 2015;Perez de Prado et al 2017). The precise role of the adventitial layer in modulating the neointimal response after coronary stenting has not been precisely established and it is controversial (Fleenor and Bowles 2009;Chang et al 2015). The aims of this study were to describe the adventitial response of porcine coronary arteries at 28 days by histomorphometric criteria and immunohistochemistry as a component of the neointimal formation and arterial remodel-ling after coronary stenting; and to analyse the role of the polymer used in relation to the adventitial response development after the DES placement.…”
mentioning
confidence: 99%
“…Hematoxylin and eosin (HE) staining was performed as previously reported ( Chang et al, 2015 ). 3 μm-thick paraffin aorta sections were stained with HE and then photographed at ×100 and ×400 magnification with a microscope for morphological analysis including intimal integrity and structure of media and adventitia.…”
Section: Methodsmentioning
confidence: 99%